Unlocking the mystery of the mid-Cretaceous Mysteriomorphidae (Coleoptera: Elateroidea) and modalities in transiting from gymnosperms to angiosperms - Peris, David; Kundrata, Robin; Delclòs, Xavier; Mähler, Bastian; Ivie, Michael A; Rust, Jes; Labandeira, Conrad C (Scientific reports, 2020)
The monospecific family Mysteriomorphidae was recently described based on two fossil specimens from the Late Cretaceous Kachin amber of northern Myanmar. The family was placed in Elateriformia incertae sedis without a clear list of characters that define it either in Elateroidea or in Byrrhoidea. We report here four additional adult specimens of the same lineage, one of which was described using a successful reconstruction from a CT-scan analysis to better observe some characters. The new specimens enabled us to considerably improve the diagnosis of Mysteriomorphidae. The family is definitively placed in Elateroidea, and we hypothesize its close relationship with Elateridae. Similarly, there are other fossil families of beetles that are exclusively described from Cretaceous ambers. These lineages may have been evolutionarily replaced by the ecological revolution launched by angiosperms that introduced new co-associations with taxa. These data indicate a macroevolutionary pattern of replacement that could be extended to other insect groups.
Keywords: počítačová rentgenová tomografie; paleontologie; Magnoliopsida; zkameněliny; Biological Evolution; Host-Parasite Interactions; zvířata; Myanmar; Cycadopsida; Coleoptera; Paleontology; Tomography, X-Ray Computed; biologická evoluce; cykasy; brouci; Amber; Animals; jantar; interakce hostitele a parazita; Fossils